Advances in novel vaccines for foot and mouth disease: focus on recombinant empty capsids. (3rd April 2019) - Mignaqui, Ana Clara; Ruiz, Vanesa; Durocher, Yves; Wigdorovitz, Andrés
Abstract: Foot and mouth disease (FMD) is a highly contagious disease of cloven-hoofed animals, which causes severe economic losses in the livestock industry. Currently available vaccines are based on inactivated FMD virus (FMDV). Although inactivated virus vaccines have proved to be effective in FMD control, they have a number of disadvantages, including the need for high bio-containment production facilities and the lack of induction of immunological memory. Novel FMD vaccines based on the use of recombinant empty capsids have shown promising results. These recombinant empty capsids are attractive candidates because they avoid the use of virus in the production facilities but conserve its complete repertoire of conformational epitopes. However, many of these recombinant empty capsids require time-consuming procedures that are difficult to scale up. Achieving production of a novel and efficient FMD vaccine requires not only immunogenic antigens, but also industrially relevant processes. This review intends to summarize and compare the different strategies already published for the production of FMDV recombinant empty capsids, focusing on large-scale production.